ANALYSIS OF THE USE OF SHARIA FINANCIAL TECHNOLOGY (FINTEK) SERVICES STUDY ON APPLICATION SERVICES AT PT. AMMANA FINTECH SHARI'AH ACCORDING TO THE FATWA OF DSN MUI AND ISLAMIC LAW - Yudha Prakarsa Karya Wiguna; Wirdyaningsih Wirdyaningsih (UNIVERSITAS PAKUAN, 2022)
The birth of Islamic financial service technology innovation (Shari'ah Fintech) has provided a lot of convenience. In practice, the community can carry out the financing collaboration process without having to meet face-to-face. However, behind all these conveniences, it is not widely known to what extent this sharia fintech application service is in accordance with the provisions of the DSN MUI Fatwa No. 117/DSN-MUI/II/2018 and also Islamic law, or is not in accordance with the legal provisions stipulated apply. This study aims to analyze the provisions of the MUI DSN Fatwa and Islamic Law on the fintech application services of PT. Ammana Fintek Syari'ah. The research method used in this study is normative juridical using a qualitative descriptive approach, namely research that aims to analyze the provisions of the Fatwa of DSN MUI and Islamic Law in theory and practice in the field. Based on the results of the study, it was found that the fintech services at PT. Ammana Fintek Syari'ah as a whole has conformity, as stated in the DSN-MUI Fatwa No. 117/DSNMUI/II/2018, including for points of general provisions, legal provisions, legal subjects, provisions related to general service guidelines and provisions related to mechanisms. contract. Meanwhile, according to Islamic law, the presence of fintech services at PT. Ammana Fintech Syari'ah has provided benefits for many people. There are two things from the five points of maqashid sharia that are maintained by the existence of PT. Ammana Fintech Syari'ah, namely, hifz al-mal (protection of property), and hifz al-nafs (protection of the soul).